NEW CORRELATION FOR OIL FORMATION VOLUME FACTOR AT AND BELOW BUBBLE POINT PRESSURE (Journal of Engineering, 2009)
The best source of oil properties data is the laboratory PVT analysis of a reservoir fluid sample. However, in the absence of experimentally measured properties of reservoir fluids, these physical properties must be estimated from correlations. This paper employs more than thirty PVT reports that have been taken from different Iraqi fields. These reports contain about four hundred experimental points.The paper suggests new correlation to calculate oil formation volume factor at and below bubble point pressure. All of the previous correlations did not take the pressure as a factor or independent variable because they calculate the oil formation volume factor at bubble point pressure only. The new correlation introduce the pressure while omit the solution gas-oil ratio which has been employed in all previous correlations. The accuracy of the proposed correlation of the experimental data is assessed through various statistical tests and comparing them with those achieved for some published correlations. These tests show that the new correlation has the best fitting with the experimental data for Iraqi oils. Cross plot technique is also applied to check the performance of the correlation and it gave the same index of the statistical criteria method. The new correlation reported absolute average error of 1.876%, sum of squared residuals of 0.395327, variance of 0.0093 and standard deviation error of 0.096337288.